Viscosity approximation methods for nonexpansive multi-valued nonself mappings and equilibrium problems - Cholamjiak P. (Warsaw University, 2014)
In this paper, strong convergence theorems by the viscosity approximation method for nonexpansive multi-valued nonself mappings and equilibrium problems are established under some suitable conditions in a Hilbert space. The obtained results extend and improve the corresponding results existed in the literature. © Faculty of Mathematics and Information Science.